Knowledge and Practice of Amran University Students toward Ear and Hearing Health - Alhouthi, Mohammed M; Al-ozaib, Nasser Y. (Journal of Amran University, 2024)
The World Health Organization (WHO) has detected an urgent need for action to prevent and manage ear diseases and hearing loss. However, the first step is to identify the areas of knowledge deficiency within the population. The aim of the study was to evaluate knowledge of university students' community in managing and preventing ear disease and hearing loss. This was a cross-sectional study conducted during February 2023 at Amran University using an online ontological questionnaire. Data was retrieved and processed in Excel spreadsheet and analyzed using SPSS version 29. A total of 330 participants responded to the online questionnaire, of whom 84.5% were male, with a mean age of 21.43 ± 1.77. Among them, 15.8% reported previous ear problems, while 41.2% had relatives with ear or hearing problems. Exposure to loud noise was reported by 37.6%, and 52.2% reported listening to headphones loudly. The overall correct response rate to the statements was 73.2%, indicating a lack of certain important knowledge. The study results showed a need for official campaigns to educate the Yemeni population. Moreover, they indicated the necessity of conducting a survey on a much wider scale to aid in the development of appropriate health communication strategies and the promotion of ear and hearing health.